Determination of Phytochemical Profile and Anti-Oxidation Activity of Annona Fruit and its Effect on Lymphoma Cell Proliferation - Al-Shaya, Huda Mohammed; Li, Haiwen; Beg, Obaid U.; A. Hamama, Anwar; Witiak, Sarah Melissa; Kaseloo, Paul; Siddiqui, Rafat A. (Challenges and Advances in Pharmaceutical Research Vol. 1, 2022)
High intake of certain vegetables and fruits is associated with a reduced risk of cancer development. We hypothesized that Annona fruit, which is rich in fibers and phytochemicals that are known to possess anti-cancer properties, can be effective in inhibiting lymphoma growth. The objective of this study was to extract the anticancer activity with a suitable solvent and determine their phenolic content and antioxidation activity. The Annona fruit’s fractions were extracted with water, methanol or chloroform solvents. Each fraction was then assayed for total phenolic, flavonoids, and tannin content, anti-oxidation activities, and inhibition of in vitro cell proliferation using the Ramos-1 lymphoma cells. The methanol fractions contained the highest phenolics, flavonoids, tannins content, and anti-oxidation activity. Although the methanol extracts of skin, pulp, and seeds had a moderate effect, the chloroform extracts of pulp and seeds had strong effects on Ramos-1 cell proliferation. Our findings suggest that Annona fruits may be effective in the prevention or treatment of lymphoma.